1990
DOI: 10.1002/path.1711600111
|View full text |Cite
|
Sign up to set email alerts
|

The blood–testis barrier in experimental unilateral cryptorchidism

Abstract: Unilateral cryptorchidism was induced in Wistar rat pups within 48 h of birth. After a period of 150 days, the blood-testis barrier was evaluated in the cryptorchid and contralateral scrotal testis, using a lanthanum immersion technique. The barrier was demonstrated to be competent, with tracer confined to the basal and intermediate compartments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Reported differences include a maintained blood-testis-barrier with cryptorchidism in rats as compared to a loss of the barrier in humans, fenestration of human testicular endothelial cells as compared to unfenestrated rat endothelial cells, and differential expression of occludin in the tight junctions between Sertoli cells in rats and humans. [20][21][22][23][24][25] While most of these differences lead one to believe penetration of NPs past the blood-testis-barrier would be greater in a human patient, if the mechanism relies upon occludin, the opposite may be true. The mechanism by which NPs cross the blood-testis-barrier has not been elucidated in this study and could be of further interest.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Reported differences include a maintained blood-testis-barrier with cryptorchidism in rats as compared to a loss of the barrier in humans, fenestration of human testicular endothelial cells as compared to unfenestrated rat endothelial cells, and differential expression of occludin in the tight junctions between Sertoli cells in rats and humans. [20][21][22][23][24][25] While most of these differences lead one to believe penetration of NPs past the blood-testis-barrier would be greater in a human patient, if the mechanism relies upon occludin, the opposite may be true. The mechanism by which NPs cross the blood-testis-barrier has not been elucidated in this study and could be of further interest.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Although the etiology of this disease is unclear, genetic factors, environmental pollution, nutrition and lifestyle are the main causes of CPT. In the testes of patients with CPT, the integrity of the blood-testis-barrier is compromised due to high temperature [9]. Indeed, high scrotal temperature induces lipid peroxidation, overproduction of reactive oxygen species (ROS) and decreases antioxidant enzymes (catalase, superoxide dismutase, glutathione peroxidase), leading to germ cells death and infertility [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Vasquez et al (6) demonstrated that the concentrations of follicle stimulating hormone, luteinizing hormone and testosterone were associated with the sperm density of patients with unilateral cryptorchidism, and that damage to the contralateral testicular was caused by endocrine abnormalities. It is additionally believed that the blood-testis barrier in unilateral cryptorchidism could be the cause of autoimmune reactions or allergic orchitis, which could then cause contralateral testis damage (7,8).…”
Section: Introductionmentioning
confidence: 99%